The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/uog.13228
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of performance of second‐trimester nasal bone assessment in detection of fetuses with Down syndrome

Abstract: Objective To review systematically the literature on diagnostic tests and performance of second-trimester sonographic assessment of nasal bone (NB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 41 publications
(97 reference statements)
1
21
2
Order By: Relevance
“…One publication reviewed over 35,000 NB examinations from nine different studies and showed that the NB was absent in 65 % of fetuses with trisomy 21 but only in 0.8 % of chromosomally normal fetuses [ 33 ]. In the second trimester, this marker becomes less predictive with absent NB seen in 30-40 % of fetuses with trisomy 21 and 0.3-0.7 % of chromosomally normal fetuses [ 34 ].…”
Section: Nasal Bonementioning
confidence: 96%
See 1 more Smart Citation
“…One publication reviewed over 35,000 NB examinations from nine different studies and showed that the NB was absent in 65 % of fetuses with trisomy 21 but only in 0.8 % of chromosomally normal fetuses [ 33 ]. In the second trimester, this marker becomes less predictive with absent NB seen in 30-40 % of fetuses with trisomy 21 and 0.3-0.7 % of chromosomally normal fetuses [ 34 ].…”
Section: Nasal Bonementioning
confidence: 96%
“…Absent NB in the second trimester was seen in 30-40 % of fetuses with trisomy 21 and 0.3-0.7 % of chromosomally normal fetuses. By considering NB hypoplasia or absent nasal bone as a single category, the fi nding was seen in 50-60 % of fetuses with trisomy 21 and 6-7 % of chromosomally normal fetuses [ 34 ]. Other ways to report hypoplasia of the NB include an absolute cutoff of <2.5 mm, gestational age-related cutoff of <2.5th or <5th percentile, a ratio of BPD/NB length or multiples of the median for gestational age with <0.75 MoM being the cutoff for abnormal NB measurement [ 35 , 36 ].…”
Section: Nasal Bonementioning
confidence: 98%
“…Abnormal facial features, such as collapse of the nose bridge, ususally indicate fetal chromosomal abnormalities. There are a number of studies suggesting that fetal nasal bone hypoplasis is an indicator of Down syndrome with relatively high sensitivity and specificity [1][2][3][4]. It is reported that the positive likelihood ratio of abnormal fetal nasal bone in screening for Down sydrome was about 11.6-50.5 [2,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, extensive researches have demonstrated that effective screening for chromosomal abnormalities can be achieved by maternal age and the ultrasonography measurement of fetal nuchal translucency thickness . The biochemical screening of free β ‐hCG and PAPP‐A for DS has been reported to achieve detection rates (DRs) of 63–83% with false positive rate (FPR) of 3–5% in the first‐trimester of pregnancy; the nuchal translucency alone has shown DRs of 69%–90% with FPR of 2–5%; hypoplasia or agenesis of the nasal bone as one of the most recently described ultrasound markers for DS screening has a pooled sensitivity of 33.6% and a specificity of 99.3% in a meta‐analysis . However, the single marker achieved unstable and low DRs, and the individual study may not have enough statistical power to estimate the performance of the screening.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] The biochemical screening of free β-hCG and PAPP-A for DS has been reported to achieve detection rates (DRs) of 63-83% with false positive rate (FPR) of 3-5% in the first-trimester of pregnancy [15][16][17] ; the nuchal translucency alone has shown DRs of 69%-90% with FPR of 2-5% 18 ; hypoplasia or agenesis of the nasal bone as one of the most recently described ultrasound markers for DS screening has a pooled sensitivity of 33.6% and a specificity of 99.3% in a metaanalysis. 19 However, the single marker achieved unstable and low DRs, and the individual study may not have enough statistical power to estimate the performance of the screening. Our aim is to estimate strength and accuracy of the different combined tests of MA and NB and NT and PAPP-A and free β-hCG for screening DS in the first-trimester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%